MICROWAVE CONTACTLESS MEASUREMENT METHOD OF SUBSTANCES LEVEL - V. V. Kazlyak; A. V. Gusinskiy; A. M. Kostrikin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis and comparison of existing contactless methods of substance level measurement is carried out. Advantages and lacks of optical, ultrasonic and microwave measurement methods are considered in details. The conclusion about expediency of a certain use contactless method of level measurement depending on set conditions is made. Microwave methods of substance level measurement are allocated as the most universal and perspective. А microwave contactless measuring instrument of substances level is considered.